Pattern of horizontal squint presentation in pediatric eye department at Civil Hospital Karachi - Tarique Saleem Shaikh; Sajida Parveen Shaikh; Waheed Ahmed Shaikh (Journal of Bahria University Medical and Dental College, 2014)
Objective: To estimate the magnitude and types of horizontal strabismus in children presenting in pediatric ophthalmic and orthoptic clinics. Materials and Methods: A prospective analytical study was conducted on strabismic children presenting in the outpatient department of pediatric ophthalmology and orthoptic clinics at Civil Hospital Karachi from 2008 to 2012. Details of patient was recorded in orthoptic performa that includedbiodata, history of presenting illness, wearing of glasses, patching treatment , previous squint surgery and family history of strabismus. Orthoptic examination as visual acuity assessment with age appropriate tests was performed. Cover test, prism cover test, cycloplegic refraction, hand mounted Slit lamp biomicroscopy and dilated fundus examination was also performed on each patient. Results: A total of 1170 children presented in the pediatrics eye department. 1074 out of 1170 (91.79%) children were diagnosed to have horizontal strabismus. Majority 429(40%) of them were up to four years of age. 698(65%) children had horizontal esotropic strabismus while 376 (35%) had horizontal exotropic strabismus. 276 (25.69 %) esotropics had concomitant constant esotropia while 244(22.7%) exotropics had constant early onset exotropia. Statistical analysis was done by using SPSS version16 Conclusion: The magnitude of horizontal squint was found to be high in children. Esotropia with concomitant constant type was the most common type of strabismus followed by exotropia of constant early onset type.